Limfadenopati Tuberkulosis dengan Drugs-induced Hepatitis (DIH) di Sikka, Nusa Tenggara Timur, Indonesia - David Denada Rahmad; Asep Purnama (Cermin Dunia Kedokteran, 2024)
Background: The most common extrapulmonary TB is lymph node TB in 35% cases of worldwide. Drug-induced hepatitis (DIH) is the possible adverse effect of antimycobacterial agents. Case: An 18-year-old male with multiple tender lumps on the right side of his neck for the last 2 weeks. Physical findings were multiple masses in the right anterior supraclavicular and submandibular region. Biopsy revealed suppurative granulomatous lymphadenitis. The diagnosis is TB lymphadenitis and the first regimen of anti-TB was given, but the patient developed nausea and vomiting and increased AST/ALT after 5 days. Anti-TB was temporarily discontinued. Anti-TB regimen was resumed after clinical and laboratory returned to normal. Conclusion: Patients with TB and DIH need to be treated individually depending on their tolerance to the drugs. Careful clinical and laboratory monitoring was needed to prevent adverse effects and for best results.